Karakterisasi Penampilan Agronomi Beberapa Varietas Bawang Merah (Allium ascalonicum) Akibat Ragam Konsentrasi Gibberellic Acid (ã€–GAã€—_3) di Dataran Rendah Kabupaten Karawang - Pranata, Priyo Bayu; Azizah, Elia; Rianti, Winda (UNIVERSITAS LABUHANBATU, 2023)
Constraints in meeting the production of shallots (Allium ascalonicum L.) caused by the use of bulbs in the previous planting season reduced the productivity of shallots. The aim of this research was to determine the best application of gibberellin concentration ( ) to improve shallot production in the lowlands of Karawang Regency. The research method used was the factorial randomized block design (RBD) experimental method consisting of 12 treatments repeated 3 times. The first factor was shallot varieties which included, namely V1 (Bima Brebes), V2 (Sumenep), V3 (Dayak) and the second factor the concentration of gibberellin ( ) included, namely G0 (0 ppm), G1 (100 ppm), G2 (150 ppm), and G3 (200 ppm). The results of the 5% level F test analysis showed no interaction in all observations. The results of the Duncan Multiple Range Test at 5% level showed that the shallot varietal factor v3 (Dayak) treatment obtained the best results on fresh weight per hill, fresh stover weight and dry stover weight. The independent factor of giberellin concentration ( ) with g0 treatment (0 ppm) showed better results on wet weight per plant and dry weight per plant.